Design and analysis of centrifugal pump impeller for performance enhancement - Selamat F.E.; Wan Izhan W.H.I.; Baharudin B.S. (UiTM Press, 2023)
Centrifugal pump usage has increased over the past year due to its importance and efficiency. Its function is to transport liquid from one place to another using energy applied to the pump. This paper revolves around the idea of design and analysis of centrifugal pump for performance enhancement within the pump specifications. Design and simulation were conducted using ANSYS CFX, using the Navier-Stokes equation. Shear Stress Transport (SST) was chosen for turbulence model for this project. From the simulation results, it can be observed that as the rotation speed of the impeller increases, the pressure within the impeller increases. The pressure increases gradually from impeller inlet to impeller outlet. It can also be observed that the efficiency of the impeller increases as the rotation speed increases. As a result, the performance of the impeller increases as the efficiency increases. Performance of the impellers was compared based on inlet and outlet power, impeller efficiency, pressure distribution, and static head pressure produced. 2016 Faculty of Mechanical Engineering, Universiti Teknologi MARA (UiTM), Malaysia.